Rethinking the Education Mess: A Systems Approach to Education Reform - Mitroff, Ian I.; Hill, Lindan B.; Alpaslan, Can M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Using a form of systems thinking, this book analyzes K-12 education as a complex,'messy' system that must be tackled as a whole and provides a series of heuristics to help those involved in the education mess to improve the system as a whole.
Keywords: Science; Science; Science, general